The Development of Generalized Motor Program in Constant and Variable Practice Conditions - Czyż, Stanisław H.; Zvonař, Martin; Pretorius, Elric (Frontiers in Psychology, 2019)
The main objective of our study was to determine whether constant and variable practice conditions lead to the development of different memory representations (GMP) and as a result, they benefit performance of a skill differently. We compared one of the Generalized Motor Program (GMP) invariant features, i.e. relative timing, of the same variation of skill developed in constant and variable practice conditions. In two experiments, participants, naïve to the basketball, were practicing free throws, receiving the same amount of practice. In constant conditions they practiced at one distance only (4.57 m), whereas in variable conditions they practiced at seven (2.74, 3.35, 3.96, 4.57, 5.18, 5.79, and 6.4 m) and five (3.35, 3.96, 4.57, 5.18, and 5.79 m) distances, in experiment 1 and 2, respectively. We found that relative timing of skills developed in constant and variable practice conditions is the same, confirming that these practice conditions form the same memory representation. However, we also observed that constant practice conditions resulted in overall shorter movement time as compared to the skill practiced in variable conditions. We hypothesized that it may be due to the facilitation of parameters assignment as it takes place in especial skill.